Terrestrial Heat Flow Density in the Zagreb – Karlovac Area - Miron Kovačić (Geologia Croatica, 2014)
Abstract Within the project „Geothermal map of the Republic of Croatia”, initiated in 2007, the wide area of the cities of Zagreb and Karlovac has been investigated (approx. 5500 km2). In this work the results of investigation of the Terrestrial Heat Flow Density (THFD) are presented. These include the results of computation of THFD at locations of boreholes and maps of THFD of the investigated area. It has been determined that THFD at the boreholes’ locations varies in a wide range and values differ from those previously published. In the most part of the investigated area THFD is in accordance with mean values for the continental areas. Two positive (Zagreb and Karlovac) and one negative (Žumberak) geothermal value can be singled out. The map of THFD, as presented in this work, is different from the previously published maps and is considerably more precise. It is determined that hydrogeothermal sources in the investigated area are not associated with THFD in the above mentioned areas.